Normalisasi Pembajakan Buku di Era Teknologi Digital - Uyun, Qurrotul (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
Piracy facilitated by digital technology has become increasingly prevalent due to the lack of awareness among perpetrators regarding the responsible use of digital tools. The rapid advancement of technology has made it easier for individuals to engage in piracy, particularly through digital media. This type of piracy often involves websites or platforms that provide plagiarized works. One of the most common forms of piracy in the digital era is the piracy of electronic books (e-books). In Indonesia, book piracy is a widespread issue, with pirated content ranging from partial to full copies of books. The growing perception that using pirated books is acceptable, particularly when they are offered at lower prices, has contributed to the proliferation of this practice. The findings of this study highlight the significant role of digital platforms in the distribution of pirated e-books, revealing that the ease of access and the economic motivations behind using pirated books are major factors driving this phenomenon. The study also identifies a lack of awareness about the legal and ethical implications of piracy, as well as the challenges in enforcing copyright laws in the digital age.